Microalbuminuria among obese and non-obese individuals: a case control study - Karthikeyan, G.; Nataraj, M. (International Journal of Advances in Medicine, 2019)
Background: Microalbuminuria among obesity cases reflects specific glomerular damage or is the marker of generalized endothelial cell dysfunction is still debatable. Thus, this study aimed to assess the presence of microalbuminuria among obese persons and non-obese individuals, who were euglycemic and normotensive. Methods: A case control study was conducted among patients attending outpatient department of general medicine in Govt Thiruvarur Medical College, Thiruvarur, for their illnesses from June 2017 to December 2017. A total of hundred participants with fifty obese cases and fifty non obese controls were included in this study. Detailed history and examination were done by the principal investigator and the same was documented in a proforma. Data entry was done using Microsoft excel and the statistical analysis includes odds ratio were calculated using Statistical Package for Social Sciences (SPSS) software version 17. Results: Among the study participants, 32% and 4% had microalbuminuria in obese and non-obese group, respectively. Also, obese participants were 11.29 times at higher chances of having microalbuminuria when compared to the non-obese patients with significant p value (p=0.002). Conclusions: Microalbuminuria can be used to predict the risk of complications in obese subjects in order to bring down the overall morbidity and mortality related to renal function.